Analisis Kesalahan Berbahasa Indonesia Pada Papan Nama Pertokoan di Jalan Singa 1 Kecamatan Tawang - Yulia Awalliyah; Reza Lestari; Nandang Kurnia Sandi; Tia Angelliani; Ai Siti Nurjamilah (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to describe language errors in writing on shop signs. Samples were taken on Jalan Singa 1, Tawang District with 4 samples of shop signboards. This paper uses a qualitative descriptive method, namely analyzing, describing and summarizing various conditions and situations from various data collected in the form of results from the field. From the results of this study, in general it can be said that Indonesian language errors in writing shop signs are still often found which do not comply with the rules of good and correct Indonesian. Forms of writing errors include errors in punctuation, abbreviations, word choice, spelling and unclear meaning. Writing errors on shop signs are caused by the influence of the use of everyday language or writing based on people's oral speech, limited knowledge of Indonesian language rules, and the tendency to simply imitate. Apart from that, people also pay little attention to how to use language in writing correctly, so these mistakes have the potential to trigger problems with language errors in writing shop signs.